How Radio Republik Indonesia Innovates and Stays Sustainable in the Digital Age: A Look at Management and Strategy - Harliantara Harliantara; Eko Wahyuanto (Jurnal Komunikasi, 2025)
Radio Republik Indonesia (RRI) is a public broadcaster that is facing many challenges in the digital age. These include going digital, creating sustainable business models, creating quality content, transparent and professional management, and developing skilled workers. This study sought new management ideas to make RRI more competitive and sustainable. Researchers have used a qualitative approach to review the books, journals, and documents of Indonesian public broadcasters. They collected and analysed the data and documents. Successful management requires creating engaging content, using digital technology, building sustainable business models, effectively managing resources, maintaining good governance, and forming partnerships. RRI needs to use digital technology wisely, find new funding sources, create content that attracts audiences, practice good governance, and train skilled workers to remain relevant and competitive. By focusing on these areas, RRI can improve its competitiveness and sustainability in the digital world. This study aimed to create a new management model and policy recommendations to strengthen the role of RRI in the digital era.